The Effect of Role Playing Method on The Socialization Skills of School-Age Children: Pre-Experiment Study at SDN Ngoro 3 Mojokerto, Indonesia - Inna Ilma Nafi'ah; Aida Novitasari; Miadi; Kiaonarni Ongko Waluyo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Bullying among school-aged children remains a significant public health and educational concern that negatively affects psychological well-being, emotional stability, self-esteem, and socialization abilities. Inadequate social skills may hinder children’s ability to interact effectively with peers and adapt to their social environment. Interactive educational approaches, such as role-playing, are considered beneficial in promoting communication, cooperation, empathy, and self-control among children. However, empirical evidence regarding the effectiveness of role-playing methods in improving socialization skills among elementary school students in Indonesia remains limited. Therefore, this study aimed to analyze the effect of the role-playing method on the socialization skills of school-aged children at SDN Ngoro 3 Mojokerto, Indonesia. This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The participants consisted of 30 fifth-grade students selected through a total sampling technique. The intervention involved three role-playing sessions conducted weekly. Socialization skills were measured using the teacher version of the Social Skills Rating System (SSRS) questionnaire before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test with a significance level of 0.05. The findings demonstrated a significant improvement in students’ socialization skills following the intervention. Before the intervention, most students (66.67%) were categorized as having moderate socialization skills, whereas after the intervention, the majority (90%) achieved high socialization skill levels. Statistical analysis revealed a significant difference between pretest and posttest scores (Z = -4.796; p = 0.000). These results indicate that the role-playing method effectively enhances children’s social interaction, cooperation, and self-control. In conclusion, role-playing is an effective and practical educational strategy for improving socialization skills among school-aged children. Integrating role-playing activities into school learning programs may contribute to fostering positive peer relationships and reducing social difficulties among elementary school students.